(untitled) (Bangladesh Journal of Medical Science, 2019)
Objective. The purpose of thisstudy was to determine the chronic toxicity of the drug “Harmine hydrochloride, capsules” for preclinical evaluation of its safety. Materials and methods.The experiment was performed on 48 CD-1 rats. Harmine hydrochloride was injectedto the animals intragastrically at doses of 2.5 mg / kg/per day, 5 mg / kg/per day, 9 mg / kg/per day, 10 mg / kg/per day for 3 months. After 3 months, the animals were withdrew from the experiment, internal organs (brain, heart, spleen, adrenals) were weighed and set in 10% neutral formalin. Histological specimenswere mounted in accordance with standard procedures. Results and Discussion. All morphological, histopathological changes, in addition to mortality and bodyweight changes were recorded.Microtome cuts, 5 micrometers thick, were stained with hematoxylin and eosin. Conclusion. As a result of the morphological study, there was no toxic effect of harmine hydrochloride at doses of 2.5 mg / kg, 5 mg / kg, 9 mg / kg and 10 mg / kg on the brain, at doses of 2.5 mg / kg and 5 mg / kg on the structure of the heart, spleen and adrenal glands. At doses of 9 mg / kg and 10 mg / kg, there is an initial toxic dose-dependent effect on the heart, spleen and adrenal glands. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.598-606